SOCIOLOGICAL ANALYSIS OF SOCIAL SECURITY OF A MODERN LARGE RUSSIAN ENTERPRISE - Anna P. Kareeva (Векторы благополучия: экономика и социум, 2021)
The relevance of the study is determined by the presence in modern society of a significant number of risks and the desire of people living in it to protect themselves from their negative impact. Social life in such a risky society is characterized by uncertainty. Institutional risk environments encompass both individual social groups and all of humanity. At the same time, security acts as a restraining element that does not allow destroying the existing social structure of a given society, and social security is capable of mitigating the social risks arising in it. Purpose of the work is to study the social security of a modern large Russian enterprise, create a theoretical model and carry out its practical analysis. Methods. The works of scientists who formed the main approaches to understanding the concept of «risk society», the theory of institutional matrices, social security, sociology of labor and the universal sociological paradigm became the theoretical and methodological base of the research. As part of the study, a socio-historical analysis of open documentary sources, a content analysis of print media, a questionnaire survey and a comparative analysis of the views of the management and employees of individual industrial enterprises of the nuclear industry were carried out. Results. The main characteristics of social risk are revealed and its definition is given, the social sphere of a modern risk-generating society is described. At the same time, security is considered as the basic social institution of such a society. It highlights the «internal structure» of the institution and its institutional forms. One of these forms defines social security. The analysis of the social security of a large Russian enterprise was carried out at various levels of society (macro-, meso- and microlevels), and a theoretical model was created. A practical analysis of the theoretical model of social security was carried out at individual industrial enterprises of the nuclear industry. Such enterprises are MCC (Zheleznogorsk, Krasnoyarsk Territory), SHK (Seversk, Tomsk Region), PA Mayak (Ozersk, Chelyabinsk Region) and Atomflot (Murmansk, Murmansk Region).